Massive access technology in 6G cellular Internet of things network - Feiyan TIAN; Xiaoming CHEN; Caijun ZHONG; Zhaoyang ZHANG (物联网学报)
To realize Internet of everything (IoE),the 6G cellular Internet of things (IoT) network need to provide wireless access with low power,massive connectivity and wide coverage.Through the analysis and research on the massive access technology in 6G cellular IoT network,especially in combination with the sporadic characteristics of IoT applications,a new access framework based on the grant-free random access protocol was designed to facilitate efficient massive access with limited spectrum resources.The proposed framework consisted of two phases.One was joint activity detection and channel estimation.The other was data transmission,which was divided into two categories,uplink data transmission and downlink data transmission,according to the different directions of data transmission.Due to the uncertainty of channel state information at the base station under the massive grant-free random access and considering the low power demand of 6G IoT devices,two robust uplink and downlink access algorithms were designed by maximizing the system energy efficiency.Extensive simulation results validate the effectiveness and robustness of the proposed algorithm.